The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/0363546516638082
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Trends in the Treatment of Meniscal Tears

Abstract: This study provides insight into the current practice trends of recent orthopaedic training graduates in the treatment of meniscal tears. The results suggest that reported meniscal procedures have decreased overall among ABOS candidates but that meniscal repair cases have increased. The findings support the recent shift toward evidence-based medicine, with changing practice patterns that may reflect the dissemination of recent findings from large, high-quality research studies in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(17 citation statements)
references
References 21 publications
0
16
1
Order By: Relevance
“…Previous studies in the US have reported an increasing number of meniscus repairs performed at the same time as ACL reconstructions. [ 48 , 49 ] This is not surprising given the increased education in the recent years regarding the chondroprotective effects of meniscus preservation. [ 49 ] Conversely, in a study conducted in Brazil, Astur et al[ 50 ] demonstrated that less than 2% of knee surgeons in both public and private health care systems routinely perform meniscal repair at the same time as ACLR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the US have reported an increasing number of meniscus repairs performed at the same time as ACL reconstructions. [ 48 , 49 ] This is not surprising given the increased education in the recent years regarding the chondroprotective effects of meniscus preservation. [ 49 ] Conversely, in a study conducted in Brazil, Astur et al[ 50 ] demonstrated that less than 2% of knee surgeons in both public and private health care systems routinely perform meniscal repair at the same time as ACLR.…”
Section: Discussionmentioning
confidence: 99%
“…As stated above, the physiotherapist had access only to the ME without imaging to make the triage recommendation. Recent evidence proposes that pain, functional limitations and clinical symptoms should be used as surgical eligibility criteria for ACL injuries [ 45 ], meniscal injuries [ 46 , 47 ] and knee OA [ 48 , 49 ] and not systematically rely on imaging results. In our study, 82% (116/142) of secondary care participants and 92% (34/37) of primary care participants were referred to conservative care after their first consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Nationwide studies of trends in meniscectomy and meniscus repair illuminate how the clinical evidence base influences the selection of surgical techniques. Three previous studies from the United States showed divergent trends in arthroscopic meniscus surgery; one of them reported a decrease in cases of meniscectomy per surgeons [ 31 ], while the other two showed that the incidence of meniscectomy was stable or increasing [ 16 , 32 ]. As for meniscus repair, two of them reported an increase in meniscus repair [ 16 , 31 ], but the proportion undergoing meniscus repair was still substantially lower than meniscectomy, even among young patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%